2020
DOI: 10.2174/1389200221666200302124102
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Baicalin Zinc Supplementation Alleviates Oxidative Stress and Enhances Nutrition Absorption in Deoxynivalenol Challenged Pigs

Abstract: Background: Deoxynivalenol contamination is increasing worldwide, presenting great challenges to food security and causing great economic losses in the livestock industry. Objective: This study was conducted to determine the protective effect of baicalin zinc as a dietary supplement on pigs fed with a deoxynivalenol-contaminated diet. Method: A total of 40 weaned pigs (21 d of age; 6.13 ± 0.42 kg average BW) were randomly assigned (10 pigs/group) to 4 dietary treatments: basal diet (Con group), basal diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Upregulation of antioxidant enzymes (SOD, CAT, and glutathione S-transferase) resulted from L. plantarum AS1 in the colon of cancer-bearing subjects suggests an anticancer benefit of this probiotic through its antioxidant attributes (57). In case of piglets, since previous studies have shown that weaning or diet contamination could cause the disordered intestine of piglets where the occurrence and the development of oxidative stress are common (58,59). Dietary supplement including some chemical complexes or microorganisms have been reported to have positive influence on the oxidative stress (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of antioxidant enzymes (SOD, CAT, and glutathione S-transferase) resulted from L. plantarum AS1 in the colon of cancer-bearing subjects suggests an anticancer benefit of this probiotic through its antioxidant attributes (57). In case of piglets, since previous studies have shown that weaning or diet contamination could cause the disordered intestine of piglets where the occurrence and the development of oxidative stress are common (58,59). Dietary supplement including some chemical complexes or microorganisms have been reported to have positive influence on the oxidative stress (59).…”
Section: Discussionmentioning
confidence: 99%
“…In case of piglets, since previous studies have shown that weaning or diet contamination could cause the disordered intestine of piglets where the occurrence and the development of oxidative stress are common (58,59). Dietary supplement including some chemical complexes or microorganisms have been reported to have positive influence on the oxidative stress (59). For instance, Baicalin-zinc or -copper is capable of exerting antioxidant capability in deoxynivalenol-challenged piglets, which is reflected in the reduction of HO-1, NQO-1, NF-κB (60, 61).…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that Baicalin alleviates macrophage damage caused by bacteria. Zha had been reported that Baicalin Zinc or Baicalin‐Copper has anti‐oxidant effects in Deoxynivalenol Challenged Pigs 23,24 . Baicalin is a key flavonoid found in the root of Scutellaria baicalensis Georgi , and it is known to have different biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Zha had been reported that Baicalin Zinc or Baicalin-Copper has anti-oxidant effects in Deoxynivalenol Challenged Pigs. 23,24 Baicalin is a key flavonoid found in the root of Scutellaria baicalensis Georgi, and it is known to have different biological activities. Combined with the results of the current study, it can be fully confirmed that Baicalin has anti-oxidant effects.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation